Intraradicular dentine silanization by a new silicon-based endodontic sealer. (September 2016) - Patiño-Herrera, Rosalba; Rueda, Juan Angel Morales; Fonseca, Cesar Gaitan; Cuisinier, Frédéric; Pérez, Elías
Abstract: We synthesize a new silicon-based endodontic sealer that reacts at room and body temperature. The sealer is initially hydrophilic allowing flowing and filling every accessory tubule of the root canal and turns hydrophobic during polymerization. A hydrophobic surface of dentinal walls could limit fluid penetration by reversing capillary pressure and reducing the space between the intraradicular dentinal wall and the endodontic sealer by covalent bonds. For this purpose, we did a surface treatment on dentinal walls to expose hydroxyl groups usable for silanization by a covalent attachment between the tetraethyl orthosilictate (TEOS) and dentinal wall, transforming dentin walls in a hydrophobic surface; while TEOS also acts as cross-linking of the sealer which ensured a good sealing. The sealer polymerization was followed by Fourier transform infrared spectroscopy (FTIR), Quartz crystal microbalance (QCM-D), water contact angle (WCA) and rheological analysis. Radiopacity, resistance to dislodgment and dimensional alterations are in accordance with international standards (ISO standard 6876/2002). Working and setting time may be manipulated by varying TEOS and catalyst concentration. Zero filtration was obtained in the liquid filtration test.